Liquid-liquid equilibrium phase diagrams of new aqueous two-phase systems : Ucon 50-HB5100 + Ammonium Sulfate + water, Ucon 50-HB5100 + Poly(vinyl alcohol) + water, Ucon 50-HB5100 + Hydroxypropyl Starch + water, and Poly(ethylene glycol) 8000 + Poly(vinyl alcohol) + water - Pereira, Martinha (2004)
The phase diagrams of Ucon 50-HB-5100 (Ucon) + ammonium sulfate (NH4)(2)SO4 + water, Ucon 50-HB-5100 + poly(vinyl alcohol) 10000 (PVA 10000) + water, Ucon 50-HB-5100 + hydroxypropyl starch (Reppal PES 100) + water, and poly(ethylene glycol) 8000 (PEG 8000)-PVA 10000 systems were determined at 22 degreesC. Measurements at 30 and 40 degreesC were also done for each Ucon-salt system. A linear regression was used to calculate the slope and standard deviation for each tie line. The standard deviations are in most situations lower than 0.1, and the tie-line slopes for each phase diagram vary within 5.5% around the medium value for all cases with the exception of the Ucon + (NH4)(2)SO4 + water system at 40 degreesC. The phase diagrams of the Ucon + (NH4)(2)SO4 + water system at different temperatures were shown to have a smaller amount of salt and polymer than conventional systems and to be thermoseparating, versatile, and particularly attractive, since phase formation is temperature-dependent. The phase diagrams of Ucon + PVA 10000 + water, Ucon + PES + water, and PEG + PVA 10000 + water systems were very similar, since high polymer concentrations (PES or PVA 10000) are required to form the two phases.